Androgen Receptor Targeted Therapy + Radiotherapy in Metastatic Castration Resistant Prostate Cancer - Massaro, Maria; Facondo, Giuseppe; Vullo, Gianluca; Aschelter, Anna Maria; Rossi, Alessandro; De Sanctis, Vitaliana; Marchetti, Paolo; Osti, Mattia Falchetto; Valeriani, Maurizio (Frontiers in Oncology, 2021)
Objectives To investigate whether radiotherapy as metastasis-directed therapy (MDT) on oligo-progressive sites in metastatic castration-resistant prostate cancer (mCRPC) patients during treatment with androgen receptor-targeted therapy (ARTT) may lead to control resistant lesions, prolonging ARTT. We analysed progression free survival, overall survival and prognostic parameters that can identify patients that best suit to this approach. Patients and Methods Retrospective analysis of a total of 67 lesions in 42 mCRPC patients treated with ablative or palliative RT to oligoprogressive lesions during ARTT. Twenty-eight patients (67%) underwent ARTT with Abiraterone acetate and 14 patients (33%) underwent ARTT with Enzalutamide. Median time between the start of ADT and ARTT beginning was 50.14 months (range 3.37-219 months). We treated 58 lesions (87%) with 3D conformal radiotherapy (3DCRT) and nine lesions (13%) with stereotactic body radiotherapy (SBRT). The Kaplan Meier method was used to assess the median overall survival (OS) and the progression-free survival (PFS). Results Median follow-up was 28 months (range 3-82 months). Median OS was 32.5 months (95% CI 25.77-39.16), 1 and 2-year OS were 71.6% and 64.1%, respectively. Median PFS was 19,8 months (95% CI 11.34–28.31), 1 and 2-year PFS were 67.2% and 47.4%, respectively. Median OS for patients that underwent radiotherapy before 6 months from the start of ARTT was 23.4 months (95% CI 2.04-44.89) and 45.5 months (95% CI 31.19-59.8) for patients that underwent radiotherapy after 6 months (p = 0.009). Conclusion Local ablative radiation therapy directed to progressive metastasis is a non-invasive, well tolerated treatment with efficacy on prolonging clinical benefit of systemic therapies with ARTT. Patients who underwent RT >6 months from the start of ARTT presented a statistically better OS and PFS compared with patients who underwent radiotherapy <6 months from the start of ARTT.